Gambaran Kasus Kematian Akibat Kekerasan Tajam Pada Jenazah di Rumah Sakit Bhayangkara Raden Said Sukanto Tahun 2021 - Dinda Amay Puspita; Asri Megaratri Pralebda; Zainal Abidin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Death was defined as the ceasing of body’s biological activities in an individual characterized by the cessation of brain, cardiovascular, and respiratory function. One of the causes of mortality was sharp object. This study aims to describe the characteristics of death due to violence using sharp object on cadavers at Bhayangkara Hospital Raden Said Sukanto in 2021 based on medical record. This is a cross-sectional descriptive study. Variables measured including age, gender, injury type and location, and the origin of the request for a postmortem (SPV). Data was analyzed using univariate data analysis performed on 34 cases. The result showed that most cases were on adolescent (18 – 25-year-old) which was 26.4%. Most were male (91.2%). Injury was located mostly on chest (47.1%). The majority of injury type was stabbing wound (vulnus punctum) which accounted for 64.7%. Postmortem were mostly requested by East Jakarta Metro police (24.6%).